2022
DOI: 10.1080/21645515.2022.2097818
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab added to allergen immunotherapy increased the effect of therapy in patients with severe local allergic rhinitis

Abstract: Background Allergen immunotherapy (AIT) is effective in patient with local allergic rhinitis (LAR). However, AIT may not always achieve the optimal treatment effect. Objective To present short study with clinical cases of LAR combined therapy with sublingual immunotherapy (SLIT) and omalizumab in patients with house dust mite (HDM) allergy and compared it to therapy with omalizumab alone. Methods Patients with severe LAR and hypersensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(35 citation statements)
references
References 8 publications
0
29
0
6
Order By: Relevance
“…23,24,27,29,32,34 Epinephrine was given in emergency situations. 23,28,30,37 The rescue medication score was calculated by adding the total number of daily rescue medications during the treatment and then dividing this number by the total number of days. 23,24,27,29,32 We calculated the score based on the data supplied in the trials.…”
Section: Data Extraction and Bias Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…23,24,27,29,32,34 Epinephrine was given in emergency situations. 23,28,30,37 The rescue medication score was calculated by adding the total number of daily rescue medications during the treatment and then dividing this number by the total number of days. 23,24,27,29,32 We calculated the score based on the data supplied in the trials.…”
Section: Data Extraction and Bias Assessmentmentioning
confidence: 99%
“…Eight studies [49][50][51][52][53][54][55][56] were parts of other included articles and contained no outcomes of interest. Finally, 11 articles (reporting the outcomes of nine trials) [26][27][28][29][30][31][32][34][35][36][37] were included in the review. The characteristics of the included trials are shown in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations